Freaky deaky - Leonard, Elmore, 1925-2013 (Harper, 2011)
A pair of former 1960s student activists who learned how to blow things up as part of their political education have teamed up after a prison stint and are on the loose in Detroit, out for a revenge against a former comrade who they now suspect of being an informant. Chris Mankowski of the Detroit Police Force finds himself suddenly faced with the problem of neutralizing their lust for destruction.